Cuencas y ciudades transfronterizas: el sistema urbano transfronterizo del Alto Acre - Novoa Goicochea, Zaniel I. (Pontificia Universidad Católica del Perú, 2025)
The study aims to analyze and interpret the organization of the cities located within the transboundary Alto Acre basin. This, in order to construct a comprehensive depiction of the crossborder urban system. Using a geographical methodological approach, the research examines and describes the characteristics of the border cities of Brazil, Bolivia, and Peru situated in the Alto Acre in the Amazon. The findings confirm the emergence of an urban system shaped by the cross-border relations and interactions developed among cities. Those relations have different hierarchical level. The study identifies the relative weakness of the emerging urban system, within which multiple units with differing levels of cohesion coexist. The most dynamic cities exhibit a higher degree of integration with their corresponding counterparts in the Brazilian-Bolivian and Brazilian-Peruvian urban systems.

El estudio tiene como objetivo analizar e interpretar la organización del conjunto de ciudades ubicadas en la cuenca transfronteriza del Alto Acre, permitiendo con ello establecer una determinada imagen del sistema urbano transfronterizo. Con apoyo del método geográfico, se analizan y describen las características de las ciudades fronterizas de Brasil, Bolivia y Perú ubicadas en el Alto Acre, zona fronteriza que comparten los tres países en este sector de la Amazonía. Se comprueba el proceso de configuración de un sistema urbano resultado de las relaciones e interacciones transfronterizas que establecen y desarrollan el conjunto de ciudades de diferente jerarquía. Se constata también la relativa debilidad del sistema urbano en formación donde coexisten varias unidades con diferente nivel de cohesión. Las ciudades más dinámicas presentan mayor integración con las correspondientes unidades del sistema urbano de Brasil y Bolivia y de Brasil y Perú.
Transboundary Basins and Cities: The Transboundary Urban System of the Alto Acre
Keywords: Urban System; City Network; Border Cities; Cross-Border Relations; Sistema urbano; Red de ciudades; Ciudades fronterizas; Relaciones transfronterizas; https://purl.org/pe-repo/ocde/ford#5.07.00